Case Report: Forensic Chemistry Analysis in Asbestos Litigation - Lúcio Paulo Lima Logrado; Caio Tadão Joko; André Lima Logrado (Brazilian Journal of Forensic Sciences, Medical Law and Bioethics)
Chrysotile asbestos, a naturally occurring fibrous silicate mineral, is extensively used in various industries due to its advantageous properties, including low cost, thermal insulation, mechanical strength, and resistance to chemical and biological degradation. However, its usage is associated with significant health risks, including mesothelioma and lung cancer, and environmental concerns due to its slow degradation and widespread contamination. Despite legislative efforts, asbestos remains a prevalent issue, particularly in countries like Brazil with significant asbestos deposits. Legislation addressing chrysotile asbestos has led to its prohibition in many countries, including Brazil. In forensic chemistry, the identification of materials suspected of containing asbestos is crucial for compliance with regulations. This study aims to showcase chemical and physical analyses conducted on samples from a real investigation involving a metallurgical company accused of using asbestos-containing materials. Various analytical techniques, including FTIR, Raman spectroscopy, SEM-EDS, XRF, and XRD, were employed, consistently identifying chrysotile asbestos in the samples despite its banishment. This case underscores the importance of forensic chemistry in identifying hazardous materials and ensuring compliance with regulatory standards.